Alterations of NK Cell Phenotype During Pregnancy in Multiple Sclerosis - Wisgalla, Anne; Ramien, Caren; Streitz, Mathias; Schlickeiser, Stephan; Lupu, Andreea-Roxana; Diemert, Anke; Tolosa, Eva; Arck, Petra C.; Bellmann-Strobl, Judith; Siebert, Nadja; Heesen, Christoph; Paul, Friedemann; et al. (Frontiers in Immunology, 2022)
In multiple sclerosis (MS), relapse rate is decreased by 70-80% in the third trimester of pregnancy. However, the underlying mechanisms driving this effect are poorly understood. Evidence suggests that CD56bright NK cell frequencies increase during pregnancy. Here, we analyze pregnancy-related NK cell shifts in a large longitudinal cohort of pregnant women with and without MS, and provide in-depth phenotyping of NK cells. In healthy pregnancy and pregnancy in MS, peripheral blood NK cells showed significant frequency shifts, notably an increase of CD56bright NK cells and a decrease of CD56dim NK cells toward the third trimester, indicating a general rather than an MS-specific phenomenon of pregnancy. Additional follow-ups in women with MS showed a reversal of NK cell changes postpartum. Moreover, high-dimensional profiling revealed a specific CD56bright subset with receptor expression related to cytotoxicity and cell activity (e.g., CD16+ NKp46high NKG2Dhigh NKG2Ahigh phenotype) that may drive the expansion of CD56bright NK cells during pregnancy in MS. Our data confirm that pregnancy promotes pronounced shifts of NK cells toward the regulatory CD56bright population. Although exploratory results on in-depth CD56bright phenotype need to be confirmed in larger studies, our findings suggest an increased regulatory NK activity, thereby potentially contributing to disease amelioration of MS during pregnancy.